806 Barriers to screening and diagnosis of obstructive sleep apnea during inpatient traumatic brain injury rehabilitation. (3rd May 2021) - Cotner, Bridget; Nakase-Richardson, Risa; Gius, Becky; Fournier, Lauren; Watach, Alexa; Hoffman, Jeanne
Abstract: Introduction: Obstructive Sleep Apnea (OSA) is prevalent after moderate to severe traumatic brain injury (TBI) and may diminish recovery when left untreated. Despite the demonstrated importance of treating OSA following TBI, assessment for OSA during or soon after inpatient rehabilitation for TBI is limited. Little is known about barriers to implementing OSA screening and early diagnosis during inpatient rehabilitation thus hindering the translation of evidence-based OSA assessment procedures into clinical practice and potentially delaying necessary OSA treatment. The current analysis explored facilitators and barriers to implementing OSA screening tools in an inpatient rehabilitation setting from the perspectives of end user stakeholders. Methods: Patients, families, industry, clinical providers and administrators participated in a two-day meeting following completion of a diagnostic clinical trial of OSA screening and diagnostic tools during inpatient rehabilitation. Stakeholders were provided with open ended questions generated by study investigators and given the opportunity to respond on paper or a "graffiti wall" (i.e., white board). Example questions include "What are the greatest needs of the healthcare system related to sleep apnea and TBI?" and "What are the key things we need to consider to move results into real-world practice?" Qualitative content analyses using a rapid matrix approach were conducted from stakeholder feedback obtained during the two-day meeting, which included a guided review of emerging OSA research and discussion of potential implementation barriers of OSA assessment during inpatient rehabilitation. Results: Improved screening and treatment practices for OSA were the greatest needs identified. To meet these needs, stakeholders identified the importance of improving patient, family, and staff understanding of OSA (e.g., health literacy) and other sleep disorders through education; inpatient rehabilitation access to resources (technology; sleep providers); and reimbursement for additional inpatient procedures. Conclusion: Although treatment of OSA is crucial for recovery during inpatient rehabilitation following TBI, barriers to earlier recognition, diagnosis, and treatment of OSA exists across several different domains, including education, resources, and funding policies. Findings support future implementation efforts to translate evidence-based care into practice to improve patient outcomes. Support (if any): PCORI-NCT03033901